#27: Comparison of RT-PCR Cycle Threshold Values from Respiratory Specimens in Symptomatic and Asymptomatic Children with SARS CoV-2 Infection. (28th June 2021) - Strutner, John; Ramchandar, Nanda; Dubey, Shruti; Gamboa, Mary; Vanderpool, Michelle K; Mueller, Teresa; Wang, Wei; Cannavino, Christopher; Padua, Leidy Tovar; Malicki, Denise; Pong, Alice
Abstract: Background: Understanding viral kinetics of SARS-CoV-2 is important to assess risk of transmission, manage treatment, and determine the need for isolation and protective equipment. Children have been noted to have less severe illness than adults and may have less transmission potential. We sought to determine whether children deemed to be asymptomatic had a difference in the PCR cycle threshold (Ct) value of respiratory samples from symptomatic children with SARS CoV-2 infection. Methods: This was a retrospective cross-sectional study to compare PCR Ct values of 728 children who tested positive for SARS-CoV-2 by respiratory samples collected over a 4-month period. The study was a single center review of patients who tested positive for SARS-CoV-2 by RT-PCR from a respiratory specimen at a large tertiary care children's hospital. Inclusion criteria included children 0–18 years of age who tested positive for SARS-CoV-2 by RT-PCR from a respiratory specimen for whom clinical information was available in the electronic medical record. Results: We analyzed 728 children who tested positive for SARS-CoV-2 by RT-PCR from a respiratory sample over a 4-month period and for whom data was available in the electronic medical record. Overall, 71.2% of infected children were symptomatic. The mean Ct value for symptomatic patients (Ct mean 19.9, SD 6.3) was significantly lower than asymptomatic patients (Ct mean 23.5, SD 6.5) (P value < 0.001, CI 95th 2.6 - 4.6). The mean PCR Ct value was lowest in children less than 5 years of age. Conclusions and Relevance: In this retrospective review of children who tested positive by RT-PCR for SARS CoV-2, the mean Ct was significantly lower in symptomatic children and was lowest in children under 5 years of age.